2021
DOI: 10.1080/21655979.2021.1952817
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile and identification of novel microRNA biomarkers for metabolic syndrome

Abstract: The lack of efficient biomarkers is the main reason for the inaccurate early diagnosis and poor treatment outcomes of patients with metabolic syndrome (MetS). The current study aimed to identify several novel microRNA (miRNA) biomarkers for metabolic syndrome via high-throughput sequencing and comprehensive bioinformatics analysis. Through high-throughput sequencing and differentially expressed miRNA (DEM) analysis, we first identified two upregulated and 36 downregulated DEMs in the plasma samples of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Moreover, higher circulating levels of serum hsa-miR-1323 has been associated with GDM [34], hsa-miR-517-5p and hsa-miR-520a-5p were reported to be downregulated in PE, which is consistent with our results with maternal BMI [16,35]. Finally, lower circulating levels of hsa-miR-526b-5p were detected in patients with metabolic syndrome -characterized by central excess adiposity-a direction of association that is concordant with our results [36]. Through their mechanism of action, the miRNAs that we found associated with maternal BMI might potentially have a role to play in the pathophysiology of how excess weight in early gestation may lead to pregnancy complications.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, higher circulating levels of serum hsa-miR-1323 has been associated with GDM [34], hsa-miR-517-5p and hsa-miR-520a-5p were reported to be downregulated in PE, which is consistent with our results with maternal BMI [16,35]. Finally, lower circulating levels of hsa-miR-526b-5p were detected in patients with metabolic syndrome -characterized by central excess adiposity-a direction of association that is concordant with our results [36]. Through their mechanism of action, the miRNAs that we found associated with maternal BMI might potentially have a role to play in the pathophysiology of how excess weight in early gestation may lead to pregnancy complications.…”
Section: Discussionsupporting
confidence: 92%
“…MicroRNAs (miRNAs) are a class of small RNA molecules with a single-stranded structure that act complementarily to mRNAs to control protein synthesis via the degradation and suppression of protein translation [ 1–3 , 24–27 ]. Increasing evidence has demonstrated that miRNAs play fundamental roles in almost all biological processes and serve as multifunctional mediators of cell growth and multiplication, cell differentiation, programmed cell death, and organ remodeling [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hsa-miR-4697-3p level, which was upregulated in Cancer in the present study, was reported to show a significant correlation with the blood glucose level and was upregulated in metabolically unhealthy subjects [ 40 ]. Hsa-miR-518e-5p, which was downregulated in Cancer in the present study, was reportedly downregulated in patients with metabolic syndrome [ 41 ]. In addition, patients who were successfully treated for DM showed the opposite trend in miRNA expression.…”
Section: Discussionmentioning
confidence: 81%